Implementing environmental and resource management - Schmidt, Michael Prof. Dr.-Ing; Onyango, Vincent; Palekhov, Dmytro (Springer, 2011)
This book represents the collected works of Environmental and Resource Management (ERM) Alumni as well as young professionals and researches who are involved in the field of ERM. The connecting theme of these works is the successful implementation of ERM in a wide range of issues including: energy innovation and management, climate change response and sustainable development aspects of resource management in developing countries. This book aims to expose some of the research outputs of ERM Alumni and present perspectives and critical questions of ERM application. The research results can provide empirical bases on which ERM study programmes and/or working environments can be problematised in order to more effectively meet the objectives of ERM. The intended audience of this volume is wide including potential and current ERM students who want to understand how ERM is being applied; and teachers and researchers who want to understand the roles and interactions of ERM Alumni and their workplace.